Dissolved oxygen and nitrates gradient influence marine microbial complexity and stability in Beibu Gulf - He, Qing; Chen, Qingxiang; Qin, Xinyi; Zhou, Shengyao; Nethmini, Rajapakshalage Thashikala; Jiang, Gonglingxia; Hou, Qinghua; Li, Xiaolei; Huang, Laizhen; Dong, Ke; Xie, Lingling; Li, Nan (Frontiers in Microbiology, 2025)
Environmental gradients are important for bacteria community in marine ecosystems. However, the tipping points of environmental heterogeneity and ecological responses to disturbances in marine ecosystems are still unclear. In this study, we sampled seawater from different layers of Beibu Gulf to investigate bacterial composition, diversity, network complexity and stability, and environmental thresholds. Proteobacteria (40.38%), Cyanobacteria (27.35%), and Actinobacteria (18.24%) were dominant across all three layers. Alpha diversity was higher in the bottom layer (BL), and beta diversity were greater in the middle layer (ML). Deterministic processes significantly structured bacterial communities. The BL had the most complex network, while the ML showed the highest stability. Dissolved oxygen (DO) influenced bacterial dissimilarity and community stability, while NO3− drives complexity. Segmented regression identified environmental stress thresholds: pH = 7.79, TN = 7.48 mg/L, and temperature = 27.9°C. DO thresholds for beta diversity were 6.31 mg/L, 6.25 mg/L and 5.93 mg/L across layers, and for βNTI were 6.57 mg/L and 6.24 mg/L in ML and BL. Tipping points for community stability occurred at DO levels of 6.71 mg/L, 5.80 mg/L and 5.94 mg/L. NO3− thresholds of complexity appeared in the SL (at 0.003 mg/L) and BL (0.020 mg/L) samples, but not in ML. This study provides new insights into bacterial stress resistance and community maintenance in the subtropical Gulf marine environments.